Risk factors associated with recurrence of ischemic stroke after intracranial stenting in china: a case-control study. (3rd October 2021) - Li, Guangwen; Liu, Tonghui; Ma, Xiaoqing; Gong, Wentao; Zhang, Xianjun; Wang, Hongxia; Guo, Yunliang; Ding, Yuchuan; Zhang, Yong
ABSTRACT: Objectives : To investigate the factors affecting the risk of recurrent stroke after intracranial artery stenting. Methods : This is a subgroup analysis of a prospective single-arm registry study with 20 participating sites. Patients aged 18–85 years old with symptomatic intracranial atherosclerotic stenosis caused by 70–99% stenosis combined with poor collaterals were included in this study. The median follow-up in this study was 26.4 months. Results : A total of 260 patients were recruited in this study. Ischemic stroke related to target vessel occurred in 11 patients (4.2%) from 30 days to the last follow-up. The multivariate analysis revealed age ≥60 years old (OR: 11.991, 95% CI: 1.400–102.716; p = 0.023), no smoking (OR: 0.087, 95% CI: 0.010–0.787; p = 0.030), and Mori C type (OR: 5.129, 95% CI: 1.242–21.178; p = 0.024) retained significance in the model. There was no significant difference in the ischemic stroke based on medical history of hypertension, diabetes, dyslipidemia, baseline percent stenosis, length of stenosis, residual stenosis, and different stent types. Conclusions : Recurrence of ischemic stroke after intracranial stenting may be associated with elderly age, non-smoking, and Mori C type lesion. These factors will need to be monitored in future trials of intracranial stenting. Clinical Trial Registration : URL: http://www.clinicaltrials.gov . Unique identifier: NCT01968122.